Art's Properties - Joselit, David (Book collections on Project MUSE., 2023)
"From the modern period until the present day, artworks have exhibited a well-known paradox: they promise a rich aesthetic experience and revolutionary qualities of innovation while simultaneously serving as a luxury commodity whose sale is directed toward a global class of oligarchs. Art's Properties proposes a new way of understanding this paradox, relating art's qualities-its properties-to its status as commercial property. In Art's Properties, esteemed art historian and theorist David Joselit argues that art's fundamental ontological property is its capacity to give access to experiences of alterity--the state of being other, or different. These experiences may appear as the image of a god, or the utopian dimensions of a black square on a white ground. Joselit goes on to explore artwork's relation to infinitude. As he explains, every work of art, in its material and visual qualities, can be host to an unlimited number of events and encounters with spectators, which persist through and over time. This infinitude is curtailed as art becomes property and is made to serve as a representation. In the modern period, white artists have been presumed to manifest an unmarked, supposedly neutral national character in Europe and the United States, while artists of color are often made to stand in for the identity attributed to them. In place of this dynamic of representation, Art's Properties will advocate for privileging narration over representation. While representation is finite-one thing is put in the place of another-narration has no end; it can be multiplied to encompass the many stories an artwork might enable. In focusing on the forms of narration that an artwork can contain, this book explores art's infinite aesthetic and material alterity"--